Field study on the improvement of coal gangue filling using dynamic compaction. - Qingfeng Zhang (Public Library of Science (PLoS), 2021)
In this study, dynamic compaction method was used to treat the gangue hill of the Xinglongzhuang coal mine in China, and the deep compaction of deep coal gangue was examined. The crushing characteristics and improving depth of coal gangue filling under different dynamic compaction conditions were determined. Dynamic compaction tests with different tamping energy were performed to improve the coal gangue filling. In addition, dynamic penetration tests and the foundation bearing capacity were conducted. The relationship between the tamping energy and improvement was investigated, and the optimum tamping energy, number of tamping blows, improving depth, and other dynamic compaction parameters and filling bearing characteristics were obtained. The field test results show that with increasing number of tamping blows, compaction induced deformation gradually decreased and begins to stabilize, while the optimum number of tamping blows increases with increasing ramming energy. The optimum number of tamping blows is in the range 9-11, and the effective coal gangue improving depth is in the range 6-8m, when the tamping energy is greater than 3000 kN.m. The gradation improved, and the weight percentage of the particles smaller than 4.75 mm was larger than 50%, resulting in better physical and mechanical behavior of the coal gangue filling. The coal gangue filling bearing capacity and anti-deformation ability increase with increasing tamping energy. The coal gangue filling bearing capacity reached at least 350 kPa after being improved by dynamic compaction with a tamping energy greater than 3000kN.m.